2010
DOI: 10.1103/physrevb.82.035436
|View full text |Cite
|
Sign up to set email alerts
|

Diffraction of fast atoms during grazing scattering from the surface of an ultrathin silica film on Mo(112)

Abstract: He atoms and H 2 molecules with energies of 2 keV are scattered under grazing angles of incidence ranging from 0.2°to 1.8°from the surface of a monolayer silica film grown on a Mo͑112͒. We observe for scattering along low indexed atomic strings in the topmost surface layer pronounced diffraction pattern owing to diffraction effects for the elastically scattered projectiles. The diffraction patterns are analyzed in terms of semiclassical trajectory calculations making use of interaction potentials derived from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
50
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 64 publications
4
50
0
Order By: Relevance
“…18 Beyond native oxide films formed on Si single crystal substrates, the preparation of thin crystalline SiO 2 films has been reported on Ni(111), 19 Pd(100), 20 TiO 2 (100), 21 and Mo(112). 9,[22][23][24][25][26] For ultrathin crystalline silica films grown on Mo(112) surface, it has been shown that the film is built of a single layer of corner-sharing [SiO 4 ] tetrahedra, each bonded to the Mo support by one corner oxygen atom. 9,23,24,26 In a recent communication, 27 we reported the first successful preparation of a crystalline silica film on Ru(0001) that exhibits a two-dimensional network of two layers of corner-sharing [SiO 4 ] tetrahedra and is only weakly bound to the metal surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Beyond native oxide films formed on Si single crystal substrates, the preparation of thin crystalline SiO 2 films has been reported on Ni(111), 19 Pd(100), 20 TiO 2 (100), 21 and Mo(112). 9,[22][23][24][25][26] For ultrathin crystalline silica films grown on Mo(112) surface, it has been shown that the film is built of a single layer of corner-sharing [SiO 4 ] tetrahedra, each bonded to the Mo support by one corner oxygen atom. 9,23,24,26 In a recent communication, 27 we reported the first successful preparation of a crystalline silica film on Ru(0001) that exhibits a two-dimensional network of two layers of corner-sharing [SiO 4 ] tetrahedra and is only weakly bound to the metal surface.…”
Section: Introductionmentioning
confidence: 99%
“…9,[22][23][24][25][26] For ultrathin crystalline silica films grown on Mo(112) surface, it has been shown that the film is built of a single layer of corner-sharing [SiO 4 ] tetrahedra, each bonded to the Mo support by one corner oxygen atom. 9,23,24,26 In a recent communication, 27 we reported the first successful preparation of a crystalline silica film on Ru(0001) that exhibits a two-dimensional network of two layers of corner-sharing [SiO 4 ] tetrahedra and is only weakly bound to the metal surface. This structure is a building element of layered silicate minerals (diphyllosilicates) 28 and can therefore be referred to as a silicate film.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years the FAD method was successfully applied to very different kinds of materials, ranging from insulators [4][5][6] to semiconductors [7,8] and metals [9][10][11], as well as structured films [12] and molecules [13] adsorbed on surfaces. However, in spite of the extensive experimental and theoretical work devoted to the research of FAD since its first experimental observation [4,5], the complete understanding of the underlying quantum processes is far from being achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2007, when the first experimental results for LiF(001) [1] and NaCl(001) [2] were published, the number of measurements and systems studied have increased considerably (see [3] and references therein), including a significant amount of studies using molecular projectiles [1,2,[4][5][6]. Spectra measured for molecular projectiles are richer than for atomic projectiles due to the internal molecular degrees of freedom (DOFs) [7], and therefore they are in principle a more sensitive tool for surface analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Spectra measured for molecular projectiles are richer than for atomic projectiles due to the internal molecular degrees of freedom (DOFs) [7], and therefore they are in principle a more sensitive tool for surface analysis. From a theoretical point of view, the diffraction of atomic projectiles has been widely studied [4,6,[8][9][10][11][12][13][14][15][16]. However, little attention has been devoted to molecular projectiles, beyond some classical scattering studies [17][18][19], although in this case theory can play a key role in understanding experimental results.…”
Section: Introductionmentioning
confidence: 99%